TO THE PROBLEM OF ERGONOMICS IN ART DESIGN - Хомякова, Анна; Щербина, Володимир (SWorldJournal, 2023)
This work is devoted to important issues of the scientific discipline of ergonomics, which is related to the physiological and hygienic requirements for the means of production, work, the workplace, and industrial premises. Ergonomics studies the function